TESTING OF THE ACTIVITY OF FLAVONOIDS FROM THE ETHANOL EXTRACT OF MELINJO LEAF (GNETUM GNEMON LINN.) AS AN ANTIOXIDANT - Natanael Priltius; Monica Suryani; Devina Chandra; Nadya Purba (Sean Institute, 2023)
Indonesia has various types of plants that have the potential to be developed into modern medicines. The main source of antioxidants comes from plants. Antioxidants can be defined as compounds capable of delaying, slowing down, or inhibiting oxidation reactions. An antioxidant group that has great potential has the ability to prevent the occurrence of premature aging, inflammatory diseases, and degenerative diseases. The availability of antioxidants in the body must be maintained and increased to be able to ward off free radicals. The purpose of this study was to determine or study the nature of the activity of flavonoid compounds from the ethanol extract of melinjo leaves (Gnetum gnemon Linn.), which can be used as antioxidants using the DPPH (1,1-diphenyl-2-pikrilhidrazyl) method. The sample used in this study was melinjo leaves obtained from Kutacane, Southeast Aceh. Samples were extracted using ethanol solvent, and antioxidant activity testing was carried out by visible spectrophotometry using the DPPH (1,1-diphenyl-2-picrylhidrazyl) method. This method uses an analysis of the Inhibitory Concentration of 50% (IC50) as a determination of free radical scavenging activity; this value describes the concentration of the test compound that can trap free radicals by 50%. The results of this study indicate that the IC50 value of the ethanol extract of melinjo leaves has a very strong effect, with an IC50 value of 28.92 μg/mL. In this study using quercetin as a reference solution, which has a very strong effect with an IC50 value of 6.2933 μg/mL, so it can be concluded that the ethanol extract of melinjo leaves has activity asan antioxidant using the DPPH method.